CONSIDERING ONLINE TRAINING: RESPONSE AND EXPECTATION IN THE PANDEMIC COVID-19 - Yudha Andanaprawira (Jurnal Perspektif, 2021)
E-learning in the training is becoming inevitability with condition changes due to pandemics. However, it urges the researcher to study some comparison on how the training actors give responses and expectation towards the conventional face-to-face model which once was prima donna. This study uses descriptive analytical studies and the data taken from questionnaires against 187 training participants as respondents, 7 committees, and 12 trainers or widyaiswaras. The data is processed and analyzed by using SPSS. The results yielded that the average scores of distance learning were more dominant (greater) than those in classical for all respondent’s categories (the committees, widyaiswaras, and participants). The study shows a tendency that distance training is more effective compared to classical training.